Dynamic control of mode modulation and spatial multiplexing using hybrid metasurfaces - Lin, Zemeng; Huang, Lingling; Zhao, Ruizhe; Wei, Qunshuo; Zentgraf, Thomas; Wang, Yongtian; Li, Xiaowei (Optics Express)

Post-Quantum Secure Group Signatures - Porzenheim, Laurens Alexander

Automated testing of NFV orchestrators against carrier-grade multi-PoP scenarios using emulation-based smoke testing - Peuster, Manuel; Marchetti, Michael; García de Blas, Gerardo; Karl, Holger (EURASIP Journal on Wireless Communications and Networking)

Personal Cross-Platform Reputation - Blömer, Johannes; Löken, Nils (Security and Trust Management, STM 2019)
We propose a novel personal reputation system for cross-platform reputation. We observe that, in certain usage scenarios, e.g. crowd work, the rater anonymity property typically imposed on reputation systems is not necessary. Instead, we propose a relaxed notion of rater anonymity that is more applicable in the crowd work scenario. This allows us to construct a secure personal reputation system from simple cryptographic primitives.

Dynamic Searchable Encryption with Access Control - Blömer, Johannes; Löken, Nils (12th International Symposium on Foundations and Practice of Security, FPS 2019)
We present a searchable encryption scheme for dynamic document collections in a multi-user scenario. Our scheme features fine-grained access control to search results, as well as access control to operations such as adding documents to the document collection, or changing individual documents. The scheme features verifiability of search results. Our scheme also satisfies the forward privacy notion crucial for the security of dynamic searchable encryption schemes.

Implementation and Comparison of Elliptic Curve Algorithms in Java - Scholz, Swante

Hegel on the Naturalness of Logic - Ficara, Elena (Argumenta)

PhASAR: An Inter-Procedural Static Analysis Framework for C/C++ - Schubert, Philipp; Hermann, Ben; Bodden, Eric (Proceedings of the 25th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS 2019), Held as Part of the European Joint Conferences on Theory and Practice of Software (ETAPS 2019))

Revealing the intrinsic geometry of finite dimensional invariant sets of infinite dimensional dynamical systems - Gerlach, Raphael; Koltai, Péter; Dellnitz, Michael (arXiv:1902.08824)
Embedding techniques allow the approximations of finite dimensional attractors and manifolds of infinite dimensional dynamical systems via subdivision and continuation methods. These approximations give a topological one-to-one image of the original set. In order to additionally reveal their geometry we use diffusion mapst o find intrinsic coordinates. We illustrate our results on the unstable manifold of the one-dimensional Kuramoto--Sivashinsky equation, as well as for the attractor of the Mackey-Glass delay differential equation.

Women Philosophers in Early Modern Philosophy - Hagengruber, Ruth Edith (British Journal for the History of Philosophy. Vol. 27)

Kooperation selbst bestimmt? Interdisziplinäre Kooperation und Zielkonflikte in inklusiven Grundschulen und Förderschulen - Neumann, Phillip
Cooperation between teachers and special educators is a central requirement for inclusive schools in which students both with and without special educational needs are taught together. In many studies the autonomy/equity norm is reported as a significant obstacle for cooperation. It implies that teachers strive towards a high amount of autonomy in the sense of ‘privacy in their classroom’ as a reaction to endemic uncertainties of pedagogical work and specific work conditions in schools. Nevertheless, some studies point out that general and special educators strive for and engage in intense forms of cooperation. In this study it is argued from a self-determination theory perspective that cooperation can be accompanied by high values of perceived autonomy if teachers internalized the need for cooperation as part of their professional identity. Furthermore, factors affecting the frequency of cooperation, perception of goal conflict frequency, and stress caused by goal conflicts relating to the endemic uncertainties of pedagogical work are investigated. Analyses were carried out using survey data collected from 222 general and special educators working in either inclusive primary schools, or special schools where pupils had specific special educational needs in the domain of ‘learning’. A key outcome of the study is the absence of the anticipated negative effect of cooperation on the perception of autonomy. This underlines doubts regarding the relevance of the autonomy/equity norm. In addition to that, having special educators with greater levels of experience, as well as the support of the principal through providing fixed time slots for cooperation are identified as central factors supporting cooperation in inclusive schools. Moreover, increased levels of cooperation were found to reduce the perception of goal conflict frequency and stress relating to goal conflicts for general educators. The results of the study are discussed with regard to theoretical implications,the professionalization of general and special educators and opportunities to enhance cooperation and supportive settings in inclusive schools. Die Kooperation von Lehrkräften und Sonderpädagog_innen stellt eine zentrale Bedingung inklusiver Beschulung von Schüler_innen mit und ohne sonderpädagogische Förderbedarfe dar. Als ein maßgebliches Hemmnis der Zusammenarbeit gilt das Autonomie-Paritäts-Muster. Dieses besagt, dass Lehrkräfte aufgrund spezifischer Arbeitsbedingungen und Strukturmerkmale pädagogischer Arbeit in Schule und Unterricht ein hohes Ausmaß an Autonomie i.S.v. ‚Privatheit im Unterricht‘ anstreben. Dennoch weisen Studien darauf hin, dass Lehrkräfte und Sonderpädagog_innen dennoch intensive Kooperationsformen praktizieren und anstreben. In der Arbeit wird mit einem Rückgriff auf die Selbstbestimmungstheorie argumentiert, dass Kooperation auch mit einem hohen Autonomieerleben einhergehen kann, wenn Lehrkräfte und Sonderpädagog_innen Kooperation als Teil ihrer eigenen Professionalität internalisiert haben. Zudem werden Einflussfaktoren auf die Häufigkeit von Kooperation sowie die Wahrnehmung und Belastung von Antinomien und Zielkonflikten als Strukturmerkmale des pädagogischen Handelns untersucht. Grundlage der quantitativ-empirischen Analysen ist eine Stichprobe von insgesamt 222 Lehrkräften und Sonderpädagog_innen in inklusiven Grundschulen und Förderschulen für den Förderschwerpunkt Lernen. Als ein wesentliches Ergebnis der Arbeit zeigt sich, dass negative Effekte der Kooperation auf das Autonomieerleben ausbleiben, sodass die aufgeworfenen Zweifel an der Relevanz des Autonomie-Paritäts-Musters bestärkt werden. Darüber hinaus erweisen sich die Berufserfahrung sowie der Rückhalt der Schulleitung durch geschaffene Zeitfenster im Stundenplan als relevante Einflussfaktoren auf die Häufigkeit der Kooperation von Sonderpädagog_innen in inklusiven Grundschulen. Lehrkräfte in inklusiven Grundschulen nehmen weniger Zielkonflikte und Antinomien wahr und erleben diese weniger belastend, je häufiger sie mit Sonderpädagog_innen kooperieren. Die Ergebnisse werden hinsichtlich theoretischer Implikationen, der Professionalisierung von Lehrkräften und Sonderpädagog_innen sowie Möglichkeiten der Förderung von Kooperation und kooperativer Strukturen diskutiert.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; BiLieF

Die sprechende Stadt. Stadtumbau in Paderborn um 1600 und in der Gegenwart - Süßmann, Johannes

Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Plunging into a world? A novel approach to undergraduates’ metaphors of reading - Scharlau, Ingrid; Körber, Miriam; Karsten, Andrea (Frontline Learning Research)
Although there is considerable research on and knowledge about students’ conceptual-izations of learning or academic practices and skills, the variability of these conceptu-alizations has been consistently neglected.In the present study, we address this varia-bility in the field of academic readingwith the help of a novel approach. Drawing on qualitative metaphor analysis, we report a detailed system of students’ conceptual met-aphors of reading. Ourspecific methodologicalapproach to identify the structure of these conceptual metaphorsallowsto analyze subjective agency on a lexical as well as grammatical level.The conceptual metaphors we identified by this method are markedly variable, although they create an overall impression of medium to low agency, that is a reader who is only weakly active or potent. Interrater reliability of the coding system was very good. We also report and analyze the frequency of the conceptual metaphors ina sample of 143 texts written by bachelor students.
Keywords: metaphor; conceptual metaphor; metaphor analysis; academic reading; transitivity

Welche Rolle spielen Fachkulturen heute? Bericht von einer Erkundungsstudie. - Scharlau, Ingrid; Huber, Ludwig (die hochschullehre)
With the present exploration, we aimed to answer the question whether distinct disciplinary cultures are present at today’s universities. To this purpose, we conducted 16 interviews with scholars from different disciplines. Qualitative analysis shows that disciplinary cultures in a narrow, epistemological sense (including forms of knowledge and work as well as organisation of teaching and learning) are perceived as distinct aspects of higher education and deemed important. Disciplinary cultures in a broader sense related to lifestyle and habitus, however, were hardly reported and not perceived as characteristic. Questions of social selectivity or inequality within universities were rarely touched in the interviews. Own cultures are typically described as rather heterogeneous, which is not the case for other cultures. Handling of possible cultures as well as differences by the interviewees turned out to be very cautious, at the same time restrained and respectful. Even where differences are observed or different values are revealed, there is little evidence of disputes. Consequences of these findings for research into disciplinary cultures and higher education are discussed.
Keywords: disciplinary culture; habitus; distinctions

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

Genericity in Network Dynamics - Schwenker, Sören
This thesis deals with the investigation of dynamical properties – in particular generic synchrony breaking bifurcations – that are inherent to the structure of a semigroup network as well the numerous algebraic structures that are related to these types of networks. Most notably we investigate the interplay between network dynamics and monoid representation theory as induced by the fundamental network construction in terms of hidden symmetry as introduced by RINK and SANDERS. After providing a brief survey of the field of network dynamics in Part I, we thoroughly introduce the formalism of semigroup networks, the customized dynamical systems theory, and the necessary background from monoid representation theory in Chapters 3 and 4. The remainder of Part II investigates generic synchrony breaking bifurcations and contains three major results. The first is Theorem 5.11, which shows that generic symmetry breaking steady state bifurcations in monoid equivariant dynamics occur along absolutely indecomposable subrepresentations – a natural generalization of the corresponding statement for group equivariant dynamics. Then Theorem 7.12 relates the decomposition of a representation given by a network with high-dimensional internal phase spaces to that induced by the same network with one-dimensional internal phase spaces. This result is used to show that there is a smallest dimension of internal dynamics in which all generic l-parameter bifurcations of a fundamental network can be observed (Theorem 7.24). In Part III, we employ the machinery that was summarized and further developed in Part II to feedforward networks. We propose a general definition of this structural feature of a network and show that it can equivalently be characterized in different algebraic notions in Theorem 8.35. These are then exploited to fully classify the corresponding monoid representation for any feedforward network and to classify generic synchrony breaking steady state bifurcations with one- or highdimensional internal dynamics.

Speech Processing for Digital Home Assistance: Combining Signal Processing With Deep-Learning Techniques - Haeb-Umbach, Reinhold; Watanabe, Shinji; Nakatani, Tomohiro; Bacchiani, Michiel; Hoffmeister, Bjoern; Seltzer, Michael L.; Zen, Heiga; Souden, Mehrez (IEEE Signal Processing Magazine)
Once a popular theme of futuristic science fiction or far-fetched technology forecasts, digital home assistants with a spoken language interface have become a ubiquitous commodity today. This success has been made possible by major advancements in signal processing and machine learning for so-called far-field speech recognition, where the commands are spoken at a distance from the sound capturing device. The challenges encountered are quite unique and different from many other use cases of automatic speech recognition. The purpose of this tutorial article is to describe, in a way amenable to the non-specialist, the key speech processing algorithms that enable reliable fully hands-free speech interaction with digital home assistants. These technologies include multi-channel acoustic echo cancellation, microphone array processing and dereverberation techniques for signal enhancement, reliable wake-up word and end-of-interaction detection, high-quality speech synthesis, as well as sophisticated statistical models for speech and language, learned from large amounts of heterogeneous training data. In all these fields, deep learning has occupied a critical role.

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Updatable Anonymous Credentials and Applications to Incentive Systems - Blömer, Johannes; Bobolz, Jan; Diemert, Denis Pascal; Eidens, Fabian (Proceedings of the 2019 ACM SIGSAC Conference on Computer and Communications Security - CCS '19)
In this paper, we introduce updatable anonymous credential systems (UACS) and use them to construct a new privacy-preserving incentive system. In a UACS, a user holding a credential certifying some attributes can interact with the corresponding issuer to update his attributes. During this, the issuer knows which update function is run, but does not learn the user's previous attributes. Hence the update process preserves anonymity of the user. One example for a class of update functions are additive updates of integer attributes, where the issuer increments an unknown integer attribute value v by some known value k. This kind of update is motivated by an application of UACS to incentive systems. Users in an incentive system can anonymously accumulate points, e.g. in a shop at checkout, and spend them later, e.g. for a discount.

Scaffoldingelemente zur Sprachförderung im Textilunterricht. - Stenzel, Nadja; Drumm, Sandra (ProDaZ)

Lektionen für Alexa & Co?! - Haeb-Umbach, Reinhold (DFG forschung 1/2019)
Wenn akustische Signalverarbeitung mit automatisiertem Lernen verknüpft wird: Nachrichtentechniker arbeiten mit mehreren Mikrofonen und tiefen neuronalen Netzen an besserer Spracherkennung unter widrigsten Bedingungen. Von solchen Sensornetzwerken könnten langfristig auch digitale Sprachassistenten profitieren.

Vorwort: Gender, Technik und Politik 4.0 – Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit - Weber, Jutta (Gender, Technik und Politik 4.0 – Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit, special issue of “Gender“ (Hg.: Jutta Weber/Diana Lengersdorf))

Zur Ehrenpromotion von Maria von Welser an der Fakultät für Kulturwissenschaften der Universität Paderborn - Hagengruber, Ruth (Konsens)
Keywords: Maria von Welser; Women; Media; War; Women in War; Refugees

Tagungsbericht: Musiklandschaften zwischen Pader und Rhein. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Interdisziplinäre Tagung vom 15. bis 17. Juli 2019 in Paderborn - Becker, Rieke; Lauert, Markus; Otto, Arnold

Kooperation selbst bestimmt? Interdisziplinäre Kooperation und Zielkonflikte in inklusiven Grundschulen und Förderschulen - Neumann, Phillip
Die Kooperation von Lehrkräften und Sonderpädagog_innen stellt eine zentrale Bedingung inklusiver Beschulung von Schüler_innen mit und ohne sonderpädagogische Förderbedarfe dar. Als ein maßgebliches Hemmnis der Zusammenarbeit gilt das Autonomie-Paritäts-Muster. Dieses besagt, dass Lehrkräfte aufgrund spezifischer Arbeitsbedingungen und Strukturmerkmale pädagogischer Arbeit in Schule und Unterricht ein hohes Ausmaß an Autonomie i.S.v. ‚Privatheit im Unterricht‘ anstreben. Dennoch weisen Studien darauf hin, dass Lehrkräfte und Sonderpädagog_innen dennoch intensive Kooperationsformen praktizieren und anstreben. In der Arbeit wird mit einem Rückgriff auf die Selbstbestimmungstheorie argumentiert, dass Kooperation auch mit einem hohen Autonomieerleben einhergehen kann, wenn Lehrkräfte und Sonderpädagog_innen Kooperation als Teil ihrer eigenen Professionalität internalisiert haben. Zudem werden Einflussfaktoren auf die Häufigkeit von Kooperation sowie die Wahrnehmung und Belastung von Antinomien und Zielkonflikten als Strukturmerkmale des pädagogischen Handelns untersucht. Grundlage der quantitativ-empirischen Analysen ist eine Stichprobe von insgesamt 222 Lehrkräften und Sonderpädagog_innen in inklusiven Grundschulen und Förderschulen für den Förderschwerpunkt Lernen. Als ein wesentliches Ergebnis der Arbeit zeigt sich, dass negative Effekte der Kooperation auf das Autonomieerleben ausbleiben, sodass die aufgeworfenen Zweifel an der Relevanz des Autonomie-Paritäts-Musters bestärkt werden. Darüber hinaus erweisen sich die Berufserfahrung sowie der Rückhalt der Schulleitung durch geschaffene Zeitfenster im Stundenplan als relevante Einflussfaktoren auf die Häufigkeit der Kooperation von Sonderpädagog_innen in inklusiven Grundschulen. Lehrkräfte in inklusiven Grundschulen nehmen weniger Zielkonflikte und Antinomien wahr und erleben diese weniger belastend, je häufiger sie mit Sonderpädagog_innen kooperieren. Die Ergebnisse werden hinsichtlich theoretischer Implikationen, der Professionalisierung von Lehrkräften und Sonderpädagog_innen sowie Möglichkeiten der Förderung von Kooperation und kooperativer Strukturen diskutiert.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; BiLieF; Multiprofessionelle Kooperation; Grundschule; Förderschule

Gender, Technik und Politik 4.0. Über digitalen Kapitalismus, disruptive Technologien und neue Regime der Unsicherheit. Schwerpunktheft der Zeitschrift „Gender“, Jg. 11(3/19) (Gender)

Method for Analysing Requirement Change Propagation based on a Modified Pagerank Algorithm - Gräßler, Iris; Thiele, Henrik; Oleff, Christian; Scholle, Philipp; Schulze, Veronika (Proceedings of the Design Society: International Conference on Engineering Design)
Complexity of products and systems is increasing through digitalization, interdisciplinarity as well as high technology maturity and new business models. In consequence, new product development (NPD) projects need to manage and satisfy a large number of requirements from a broad range of stakeholders. Yet, NPD projects are often delayed due to requirement changes. In this paper, a new method for analyzing requirement change propagation is presented. The method is based on the assessment of requirement interrelations structured in a requirements structure matrix by a modified page-rank algorithm. By the method, a high number of strongly interrelated requirements can be analyzed in an efficient manner. Additionally, higher-level interrelations as well as the relative weights of requirements are also incorporated in the analysis. Hereby, an efficient holistic approach towards the analysis of requirement change propagation is proposed.

The Role of Saliency in Learning First Words - Wildt, Eugenia; Rohlfing, Katharina; Scharlau, Ingrid (Frontiers in Psychology)

Gemeinsam biblischen Geschichten begegnen - reziprokes Lehren als bibeldidaktische Methode - Uppenkamp, Vera; Sarah-Luise, Weßler (Miteinander am Tisch. Tische als Ort sozialer Utopien)

Teilautomatisierte Parameteridentifikation für die Validierung von Dynamikmodellen im modellbasierten Entwurf mechatronischer Systeme - Kruse, Daniel

Almost Optimal Classical Approximation Algorithms for a Quantum Generalization of Max-Cut - Gharibian, Sevag; Parekh, Ojas (Proceedings of the 22nd International Workshop on Approximation Algorithms for Combinatorial Optimization Problems (APPROX))

The complexity of simulating local measurements on quantum systems - Gharibian, Sevag; Yirka, Justin (Quantum)

Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data

Öffentlichkeit im digitalen Kapitalismus - Fuchs, Christian (Das Ende der Vielfalt? Zur Diversität der Medien)

Appropriation of Digital Machines and Appropriation of Fixed Capital as the Real Appropriation of Social Being: Reflections on Toni Negri’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

M. N. Roy and the Frankfurt School: Socialist Humanism and the Critical Analysis of Communication, Culture, Technology, Fascism and Nationalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

What is Critical Digital Social Research? Five Reflections on the Study of Digital Society - Fuchs, Christian (Journal of Digital Social Research)

We Need a Full Public Service Internet – State-Owned Infrastructure is Just the Start - Fuchs, Christian (The Conversation)

Boris Johnson Takes His Brexit Demagoguery to the Social Media Sphere - Fuchs, Christian (TruthOut)

Straightforward Immobilization of Phosphonic Acids and Phosphoric Acid Esters on Mesoporous Silica and Their Application in an Asymmetric Aldol Reaction - Weinberger, Christian; Heckel, Tatjana; Schnippering, Patrick; Schmitz, Markus; Guo, Anpeng; Keil, Waldemar; Marsmann, Heinrich C.; Schmidt, Claudia; Tiemann, Michael; Wilhelm, René (Nanomaterials)
The combined benefits of moisture-stable phosphonic acids and mesoporous silica materials (SBA-15 and MCM-41) as large-surface-area solid supports offer new opportunities for several applications, such as catalysis or drug delivery. We present a comprehensive study of a straightforward synthesis method via direct immobilization of several phosphonic acids and phosphoric acid esters on various mesoporous silicas in a Dean–Stark apparatus with toluene as the solvent. Due to the utilization of azeotropic distillation, there was no need to dry phosphonic acids, phosphoric acid esters, solvents, or silicas prior to synthesis. In addition to modeling phosphonic acids, immobilization of the important biomolecule adenosine monophosphate (AMP) on the porous supports was also investigated. Due to the high surface area of the mesoporous silicas, a possible catalytic application based on immobilization of an organocatalyst for an asymmetric aldol reaction is discussed.

Challenging algorithmic profiling: The limits of data protection and anti-discrimination in responding to emergent discrimination - Mann, Monique; Matzner, Tobias (Big Data & Society)
The potential for biases being built into algorithms has been known for some time (e.g., Friedman and Nissenbaum, 1996), yet literature has only recently demonstrated the ways algorithmic profiling can result in social sorting and harm marginalised groups (e.g., Browne, 2015; Eubanks, 2018; Noble, 2018). We contend that with increased algorithmic complexity, biases will become more sophisticated and difficult to identify, control for, or contest. Our argument has four steps: first, we show how harnessing algorithms means that data gathered at a particular place and time relating to specific persons, can be used to build group models applied in different contexts to different persons. Thus, privacy and data protection rights, with their focus on individuals (Coll, 2014; Parsons, 2015), do not protect from the discriminatory potential of algorithmic profiling. Second, we explore the idea that anti-discrimination regulation may be more promising, but acknowledge limitations. Third, we argue that in order to harness anti-discrimination regulation, it needs to confront emergent forms of discrimination or risk creating new invisibilities, including invisibility from existing safeguards. Finally, we outline suggestions to address emergent forms of discrimination and exclusionary invisibilities via intersectional and post-colonial analysis.

Gas Responsive Nanoswitch: Copper Oxide Composite for Highly Selective H2S Detection - Paul, Andrej; Schwind, Bertram; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (Advanced Functional Materials)
A nanocomposite material based on copper(II) oxide (CuO) and its utilization as a highly selective and stable gas-responsive electrical switch for hydrogen sulphide (H2S) detection is presented. The material can be applied as a sensitive layer for H2S monitoring, e.g., in biogas gas plants. CuO nanoparticles are embedded in a rigid, nanoporous silica (SiO2) matrix to form an electrical percolating network of low conducting CuO and, upon exposure to H2S, highly conducting copper(II) sulphide (CuS) particles. By steric hindrance due to the silica pore walls, the structure of the network is maintained even though the reversible reaction of CuO to CuS is accompanied by significant volume expansion. The conducting state of the percolating network can be controlled by a variety of parameters, such as temperature, electrode layout, and network topology of the porous silica matrix. The latter means that this new type of sensing material has a structure-encoded detection limit for H2S, which offers new application opportunities. The fabrication process of the mesoporous CuO@SiO2 composite as well as the sensor design and characteristics are described in detail. In addition, theoretical modeling of the percolation effect by Monte-Carlo simulations yields deeper insight into the underlying percolation mechanism and the observed response characteristics.

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Mary (Tekniikan Waiheita)

Quasiparticle and excitonic effects in the optical response of KNbO3 - Schmidt, Falko; Riefer, Arthur; Schmidt, Wolf Gero; Schindlmayr, Arno; Imlau, Mirco; Dobener, Florian; Mengel, Nils; Chatterjee, Sangam; Sanna, Simone (Physical Review Materials)
The cubic, tetragonal, and orthorhombic phase of potassium niobate (KNbO3) are studied based on density-functional theory. Starting from the relaxed atomic geometries, we analyze the influence of self-energy corrections on the electronic band structure within the GW approximation. We find that quasiparticle shifts widen the direct (indirect) band gap by 1.21 (1.44), 1.58 (1.55), and 1.67 (1.64) eV for the cubic, tetragonal, and orthorhombic phase, respectively. By solving the Bethe-Salpeter equation, we obtain the linear dielectric function with excitonic and local-field effects, which turn out to be essential for good agreement with experimental data. From our results, we extract an exciton binding energy of 0.6, 0.5, and 0.5 eV for the cubic, tetragonal, and orthorhombic phase, respectively. Furthermore, we investigate the nonlinear second-harmonic generation (SHG) both theoretically and experimentally. The frequency-dependent second-order polarization tensor of orthorhombic KNbO3 is measured for incoming photon energies between 1.2 and 1.6 eV. In addition, calculations within the independent-(quasi)particle approximation are performed for the tetragonal and orthorhombic phase. The novel experimental data are in excellent agreement with the quasiparticle calculations and resolve persistent discrepancies between earlier experimental measurements and ab initio results reported in the literature.

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Beyond Big Data Capitalism, Towards Dialectical Digital Modernity: Reflections on David Chandler’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Introduction: Big Data Capitalism – Politics, Activism, and Theory - Fuchs, Christian; Chandler, David (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria